SAT0453 Have We Got the Eyes Right? An Audit of Referral Patterns to Opthalmology in JIA. (23rd January 2014) - Alston, C.; Evans, A.; Hull, R.
Abstract : Background: Uveitis is a complication of Juvenile Idiopathic Arthitis (JIA) and can lead to chronic visual impairment. Each type of JIA has a different prevalence. Oligoarticular onset JIA has a high risk for developing uveitis, polyarticular onset an intermediate risk. The earliest changes are only visible with a slit lamp. Patients should be reviewed regularly by an ophthalmologist. Objectives: The British Society for Paediatric and Adolescent Rheumatology (BSPAR) and Royal College of Ophthalmologists have produced guidelines on screening for uveitis. We have audited our population to see if we achieve the guideline standards. Methods: Fifty patients with JIA were randomly selected from a database. A retrospective audit was completed to see if the BSPAR guidelines for uveitis screening were followed. Results: We obtained data from 50 cases: (female 62 %, male 38 %). The mean age at presentation of JIA was 8 years and 2 months (range 17 months to 15 years and 2 months). 64%(32) had oligoarthritis, 14%(7) polyarticular arthritis, 8%(4) systemic onset, 12%(6) psoriatic type and 2%(1) had enthesitis related arthritis. 16%(4) developed uveitis, 3 cases were mild and managed with steroids and one case developed bilateral cataracts. Cases with systemic JIA do not need screening for uveitis as they are very low risk. No cases were seropositive for rheumatoid factor. Six cases were excluded from further analysis, 2 cases presented with acute anterior uveitis initially and 4 cases had ophthalmology reviews at their local trust. Guidelines recommend an ophthalmology review within 6 weeks of referral. Thirty five (88%) of referred cases were reviewed in the ophthalmology department; the mean time for first appointment was 9 weeks. 35%(14/40) of patients were seen within 6 weeks. In addition 2(5%) patients did not attend their appointments, 2(5%) cases were not referred to the ophthalmology department and 1(2%) case was referred but the appointment was cancelled and not rebooked by the ophthalmology department. Guidelines recommend that children are seen at 2 monthly intervals from the onset of the arthritis for 6 months and then at 3-4 monthly intervals. Patients on average were reviewed at 6 month intervals 69%(24) cases. Guidelines were achieved in 5%(2/35) of cases. One (3%) case was reviewed annually, 3(9%) cases were discharged after the first appointment, one inappropriately and 14%(5) did not attend their appointments. One child with longer interval appointments had uveitis and subsequently developed bilateral cataracts Conclusions: Ophthalmology screening is an important part of JIA management. Whilst the majority of 'at risk' patients were seen, there was delay in the first eye appointment. This could be related to delay in receipt of letter, central appointment booking and lack of space in clinic lists. We are currently evaluating the patterns of referral and delays. Both ophthalmology and rheumatology wish to maintain timely referral and monitoring of these patients. References: BSPAR: Guidelines for screening for Uveitis in Juvenile Idiopathic arthritis (BSPAR and RCPOphth 2006); www.arthritisresearch.org Disclosure of Interest: None Declared